2016
DOI: 10.1182/blood.v128.22.2965.2965
|View full text |Cite
|
Sign up to set email alerts
|

Improved Survival of Older Patients with Mantle Cell Lymphoma (MCL) with Front-Line Cytarabine-Based Immunochemotherapy

Abstract: Introduction While the role of cytarabine-based immunochemotherapy (ICT) and autologous stem cell transplantation (ASCT) in untreated younger patients with MCL is well established, the utility of 'more intense' approaches in older patients is uncertain. Despite a median age at presentation of 60 years or more there are few therapeutic trials focussing on older patients. With the development of targeted agents, the need to define the optimal ICT strategy for comparison is pressing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Feinberg et al [ 22 ] reported that AEs, supportive care, and treatment duration were associated with increases in hospitalizations and ER visits. The Ratnasingam et al [ 23 ] study reported increased hospitalization for patients treated with R-HyperCVAD/R-MA compared with R-CHO/R-DHAC due to greater toxicity. The Widmer et al [ 24 ] study reported that hospitalization and hematological toxicity rates were significantly higher in the R-hyper-CVAD therapy group versus the R-CHOP/HD-ASCT group.…”
Section: Resultsmentioning
confidence: 99%
“…Feinberg et al [ 22 ] reported that AEs, supportive care, and treatment duration were associated with increases in hospitalizations and ER visits. The Ratnasingam et al [ 23 ] study reported increased hospitalization for patients treated with R-HyperCVAD/R-MA compared with R-CHO/R-DHAC due to greater toxicity. The Widmer et al [ 24 ] study reported that hospitalization and hematological toxicity rates were significantly higher in the R-hyper-CVAD therapy group versus the R-CHOP/HD-ASCT group.…”
Section: Resultsmentioning
confidence: 99%
“…Cytarabine‐based chemoimmunotherapy (R‐hyperCVAD/R‐MA; R‐CHOP/R‐DHAC) significantly improved OS and PFS over a median follow up of 40 months without ASCT in patients >60 years (median age 69 years) . The use of this treatment in older patients is based on extension of the experience in younger patients where incorporation of cytarabine significantly improves outcomes; however, the toxicity is an important consideration.…”
Section: Mantle Cell Lymphomamentioning
confidence: 99%